Student's interest in PENILIK as sustainable development extracurricular program to support agricultural awareness - Yani, Mely; Layyinah, Syifa Qalbiyatul; Zahra, Ince Raudhiah; Achwani, Annie Satriani; Riandi, Riandi; Sholihat, Rini; Amprasto, Amprasto (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
This study is a descriptive study that aims to describe the implementation of the PENILIK (Pasukan Petani Cilik) Program and find out students' interest in the program to support the agricultural awareness of students. PENILIK is an extracurricular program in regenerative agriculture in a school environment that focuses on training in farming competencies, which has several stages, such as identification, analysis, implementation, and reflection. This program is an effort to implement the value of education sustainable development to increase students' interest and awareness in the agricultural area. Student's response was taken from a questionnaire given to 26 extracurricular members who are able and committed to accomplish the program at one of the schools which has high potential area for agriculture. Based on the questionnaire results, students have a high interest in the program, and the programs can positively impact students, especially in increasing their awareness of the importance of agriculture. Furthermore, this program brings an opportunity for the school and surround society to explore the agricultural potency adjust with the goals of education sustainable development. Therefore, support from all stakeholder, parents and the community involved in implementing the program's sustainability is needed.